The dimensionality and measurement of destructive instructor-leadership. Issue 2 (3rd March 2020) - Balwant, Paul T.; Birdi, Kamal; Stephan, Ute
ABSTRACT: The conceptualization of destructive leadership has received increasing attention in recent times. Accordingly, researchers have developed a theoretical model of destructive leadership that highlights two manifestations as follows: (1) leading followers towards goals that contradict the organization's interests and (2) the use of harmful methods in leading followers. The two manifestations of destructive leadership point to the concept being multidimensional. However, researchers rarely investigate the dimensionality of destructive leadership when measuring the concept in general and in instructor–student relationships. Moreover, the most prominent measure of destructive leadership fails to capture its two manifestations adequately. To address the apparent mismatch between the theory and measurement of destructive instructor-leadership, we enhance an existing measure of destructive leadership. Using a sample of 174 students from the U.K., the findings indicated that the two manifestations of destructive instructor-leadership can be measured by 13 items, and was composed of three dimensions including, irresponsibility, victimization and callous communication. These findings along with limitations and suggestions for future research are discussed.